Virus taxonomy: the database of the International Committee on Taxonomy of Viruses - Black, Eden J; Powell, C Steve; Dempsey, Donald M; Hendrickson, R Curtis; Mims, Logan R; Lefkowitz, Elliot J (Nucleic acids research, 2025)
Taxonomic classification underlies all biological science and is the basis for comparative analysis of biological organisms and therefore our understanding of life. The International Committee on Taxonomy of Viruses (ICTV) develops the official taxonomy for all viruses. To ensure that the taxonomic data, associated metadata, and analytical tools used to search and visualize those data are easily accessible, the ICTV maintains a comprehensive database and website that provides these resources to the scientific community and the interested public. This report describes the extensive enhancements made to these resources since our first Nucleic Acids Research Database Issue publication in 2018. These enhancements have focused on improvements to the computational infrastructure supporting the database, website, and tools; expanding the information available on the taxonomy and the viruses classified by that taxonomy; enhancing existing and developing new tools to access, search, and display taxonomic data; expanding the available methods and links used to access the taxonomic and associated data; and providing outreach and training opportunities to our users to ensure that these resources are useful and used. The data and tools provided through this effort are available from the ICTV website at https://ictv.global.